2014
DOI: 10.1002/aenm.201301863
|View full text |Cite
|
Sign up to set email alerts
|

On the Thermodynamics, the Role of the Carbon Cathode, and the Cycle Life of the Sodium Superoxide (NaO2) Battery

Abstract: Batteries based on the cell reaction between alkali metals and oxygen are highly attractive for energy storage due to their superior theoretical energy density. However, despite continuous progress, fundamental challenges in the further development of these cell systems remain. Understanding the oxygen electrode reaction and improving cycle life, while at the same time maximizing the practical energy density, are some of the most important issues that need to be addressed. Here, the product formation in aproti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
226
2
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(246 citation statements)
references
References 46 publications
8
226
2
10
Order By: Relevance
“…[12][13][14][15][16] Although the specific energy capacity of Na (1,166 mAh/g) is lower than that of Li metal-based battery (3,861 mAh/g), the costeffectiveness of Na metal precedes the high capacity of Li in the next-generation battery industry since it could be acquired directly even from the ubiquitous aqueous NaCl solution.…”
Section: The Property Of Na Metal As Anode Materials and Research Trendmentioning
confidence: 99%
“…[12][13][14][15][16] Although the specific energy capacity of Na (1,166 mAh/g) is lower than that of Li metal-based battery (3,861 mAh/g), the costeffectiveness of Na metal precedes the high capacity of Li in the next-generation battery industry since it could be acquired directly even from the ubiquitous aqueous NaCl solution.…”
Section: The Property Of Na Metal As Anode Materials and Research Trendmentioning
confidence: 99%
“…Recently, a metal-air battery in which lithium has been replaced by sodium has received increasing attention. 12 Although Na−O 2 batteries present lower gravimetric energies on a cell basis (1605 or 1108 Wh/kg based on Na 2 O 2 or NaO 2 discharge products, respectively) 12 much lower charge overpotentials (∼100 mV) than those in typical Li−O 2 batteries (∼1000 mV) have been reported 13,14 based on reversible sodium superoxide (NaO 2 ) formation (Na + O 2 ↔ NaO 2 , E 0 = 2.27 V). Unlike Li−O 2 batteries, for which Li 2 O 2 is the only discharge product, NaO 2 , 12−15 sodium peroxide (Na 2 O 2 ), 16,17 and sodium peroxide dihydrate (Na 2 O 2 ·2H 2 O), 18,19 or a mixture, 19−21 have been identified in Na−O 2 batteries in ether-based electrolytes using a range of carbon electrode types.…”
mentioning
confidence: 99%
“…Unlike Li−O 2 batteries, for which Li 2 O 2 is the only discharge product, NaO 2 , 12−15 sodium peroxide (Na 2 O 2 ), 16,17 and sodium peroxide dihydrate (Na 2 O 2 ·2H 2 O), 18,19 or a mixture, 19−21 have been identified in Na−O 2 batteries in ether-based electrolytes using a range of carbon electrode types. These products have been shown to have different morphologies: NaO 2 in micron-scale cubic shapes 12,14 and nanorods, 22 Na 2 O 2 in polycrystalline particles, 16 and Na 2 O 2 ·2H 2 O as rod-shaped particles or thin films. 20 Unfortunately, the factors responsible for dissimilar discharge product chemistry and morphologies are still unclear, and no correlation has been found between the type of air electrode or electrolyte and the discharge product formed.…”
mentioning
confidence: 99%
“…Evidence of the reaction intermediate superoxide in the precipitate has been reported [8][9][10][11] and it has been demonstrated that this is easier to oxidize than peroxide [12]. In effect Na/O 2 and K/O 2 cells, where superoxide prevails, have remarkably higher reversibility than Li/O 2 [13,14].…”
Section: Metal-air Batteries and The Nature Of Discharge Productsmentioning
confidence: 91%
“…Electrochemical treatments are performed using homemade cell based on the Giessen battery design [13], resulting in Swagelok-like battery arrangement. After the electrochemical treatment the cell is opened in an Ar-filled glove box and the grid washed with DME and hexane to fully remove the electrolyte.…”
Section: Sample Preparation and Transfermentioning
confidence: 99%